Analisis Segmenting, Targeting dan Positioning (STP) Terhadap Tingkat Penjualan Properti ( Studi Pada Penjualan Tanah Kavling di Jabung, Kabupaten Malang ) - Nova Kartikasari; Pardiman Pardiman; Arini Fitria Mustapita (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThis study aims to determine and analyze the effect of segmenting, targeting and positioning on the level of sale of land plots either simultaneously or partially. The method used in this research is multiple linear regression method. The research sample was 70 companies which were taken with saturated sample method. In this study using quantitative research. This type of research is explanatory research (explanatory research).The results of this study indicate that segmenting, targeting and positioning simultaneously have a significant effect on sales levels. And partially segmenting and targeting have no significant effect on the level of sales, partially positioning has a significant effect on the level of sales. Keywords: Segmenting, Targeting, Positioning, Sales Level